Development of the Gastrointestinal Dysfunction Score (GIDS) for critically ill patients – A prospective multicenter observational study (iSOFA study). Issue 8 (August 2021) - Reintam Blaser, Annika; Padar, Martin; Mändul, Merli; Elke, Gunnar; Engel, Christoph; Fischer, Krista; Giabicani, Mikhael; Gold, Thomas; Hess, Benjamin; Hiesmayr, Michael; Jakob, Stephan M.; Loudet, Cecilia I.; et al.
Summary: Background & aims: To develop a five grade score (0–4 points) for the assessment of gastrointestinal (GI) dysfunction in adult critically ill patients. Methods: This prospective multicenter observational study enrolled consecutive adult patients admitted to 11 intensive care units in nine countries. At all sites, daily clinical data with emphasis on GI clinical symptoms were collected and intra-abdominal pressure measured. In five out of 11 sites, the biomarkers citrulline and intestinal fatty acid-binding protein (I-FABP) were measured additionally. Cox models with time-dependent scores were used to analyze associations with 28- and 90-day mortality. The models were estimated with stratification for study center. Results: We included 540 patients (224 with biomarker measurements) with median age of 65 years (range 18–94), the Simplified Acute Physiology Score II score of 38 (interquartile range 26–53) points, and Sequential Organ Failure Assessment (SOFA) score of 6 (interquartile range 3–9) points at admission. Median ICU length of stay was 3 (interquartile range 1–6) days and 90-day mortality 18.9%. A new five grade Gastrointestinal Dysfunction Score (GIDS) was developed based on the rationale of the previously developed Acute GI Injury (AGI) grading. Citrulline and I-FABP did not prove their potential for scoring of GI dysfunction in critically ill. GIDS was independently associated with 28- and 90-day mortality when added to SOFA total score (HR 1.40; 95%CI 1.07–1.84 and HR 1.40; 95%CI 1.02–1.79, respectively) or to a model containing all SOFA subscores (HR 1.48; 95%CI 1.13–1.92 and HR 1.47; 95%CI 1.15–1.87, respectively), improving predictive power of SOFA score in all analyses. Conclusions: The newly developed GIDS is additive to SOFA score in prediction of 28- and 90-day mortality. The clinical usefulness of this score should be validated prospectively. Trial registration: NCT02613000, retrospectively registered 24 November 2015.